Effort to Reduce The Incidence of Anemia in Grade XII Students of SMAN 1 Sei Rampah Using The Action Research Approach - M Taufik Alfyan; Felix Kasim; Fadlilah Widyaningsih; anggraeni, Ratih (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Anemia is a condition of low hemoglobin levels in the blood. This condition often occurs in adolescent girls due to menstrual cycles and a tendency to diet. Adolescent girls who suffer from anemia are at risk of giving birth to babies with low birth weight and stunting. The incidence of anemia is very high in North Sumatra, one of which is in Sei Rampah District. Because of this condition, researchers feel the need to make efforts to reduce the incidence of anemia by providing iron tablets. The action research method was carried out to determine whether there were changes in hemoglobin levels in the anemia group of grade XII SMAN 1 Sei Rampah students who were given intervention. The students' hemoglobin levels were measured to group which ones had the potential for anemia, then given iron tablets once a week for 4 weeks and then their hemoglobin levels were measured again. Action research plays a role in achieving a decrease in the incidence of anemia. Researchers concluded that there was an increase hemoglobin levels by 96.7% in the group of female students categorized as anemic after the intervention of anemia concept education and the provision of iron tablets with assistance.